Sedimentation velocity analytical ultracentrifugation discrete species and size-distributions of macromolecules and particles - Schuck, Peter William 1968- (CRC Press, Taylor & Francis Group, 2016)
"The analysis of sedimentation velocity analytical ultracentrifugation has fundamentally changed in the last two decades, with the ability to solve the master equation of the sedimentation/diffusion process and the application of modern mathematical data analysis strategies substantially increasing hydrodynamic resolution of sedimenting particles. This book provides a systematic introduction to the theory of sedimentation velocity, and a comprehensive overview of experimental design strategies and data analysis. Areas of major focus are polydisperse macromolecules and nanoparticles, and the sedimentation of systems of reversibly interacting macromolecules, including protein interactions"...
Includes bibliographical references and index
Keywords: Ultracentrifugation; Macromolecules -- Analysis; Nanoparticles -- Analysis; Sedimentation analysis